Persistência de mamíferos de médio e grande porte em fragmentos de floresta ombrófila mista no estado do Paraná, Brasil - Brocardo, Carlos Rodrigo [UNESP]; Candido Junior, Jose Flavio (Univ Federal Vicosa, 2012)
The Araucaria Forest is now represented by remnants of what was a continuous area of about 200,000 km(2). Medium and large mammals inhabiting this forest have suffered the impacts from the disturbance process and environmental degradation. Thus, this study determined which medium and large mammal species still inhabit the remnants of this vegetation type in Western Parana State. Three study areas, with 520, 405 and 135 hectares, consisting of stretches of primary forest mixed with secondary forest, were considered for mammal inventory. The evidence of mammals was verified directly (views) and indirectly (traces, trichology and interviews with local dwellers). It was recorded 32 species (including one exotic and two small ones), belonging to eight orders and 18 families. Nine animals of these species are at risk of extinction in the Parana State and five configure with insufficient data in the List of Endangered Species of the state. The results of this study indicate the great importance of these forest fragments in the conservation of several medium and large mammals in the Araucaria Forest of Parana State. Nevertheless, due to the negative pressures that these areas have been suffering, immediate and concrete public actions are required to ensure the maintenance of these mammal populations.
Persistence of large and medium mammals in araucaria forest fragments in paraná state, Brazil
Keywords: Forest fragmentation; Araucaria angustifolia and Hunting